PENGARUH PERSEPSI PADA KTSP, KEPEMIMPINAN KEPALA SEKOLAH, DAN PENGUASAAN TIK TERHADAP KINERJA GURU SMA (STUDI EMPIRIS DI KABUPATEN CILACAP) - Mujiyono, Eko (Sainteks, 2012)
This study entitled “Influence of Perception on School Based Curriculum (SBC), The School Principal Leadership, and Teachers’ mastery of ICT on Performance of SMA (Empirical Studies in Cilacap Regency)”. The purpose of this study is to make known and analyze the influence of perception on SBC, perception on the Principal leadership , and teacher’s mastery of ICT on the performance of Senior high school teachers as well as to analyze which one of the three factor’s most dominantly effects the improvement of high school teacher’s performances in Cilacap Regency (district).The study was conducted in both state and private high school in Cilacap Regency held from 29 March to 30 April 2012. This study is a survey that took the case on the performance of high school teachers in the regency of Cilacap, by taking a sampling of data using cluster random sampling method. As the samples are the high school teachers in Cilacap regency totaling 73 teachers who teach in 33 state or private high school. The clusters are the schools that are grouped in to 4 SMA sub rayon ( sub-district), each sub district consisting of different number of schools. In the schools that have more than or equal to 18 classes, three teachers taken, meanwhile in the school that have less than 18 classes are taken two teachers as a sample. The population in this study were all high school teachers in the regency who teach in 44 schools totaling 629 government teachers and non government who ranged doubled. The analytical tool used in this study is multiple linear regression analysis, while to test the level of significance is used the F test and t test. The result of multiple linear regression analysis shows the equation : Ŷ = - 9.160 + 0.382 X1 + 0.286 X2 + 1.240 X3 + e Multiple correlation analysis of the linear regression model was found to be the value of 0.888 or 88.80 percent, which means the relationship between the independent variables with the dependent variable is very strong. The value of coefficient of determination (R2) of 0.779 or 77.90 percent mean that variation of variables in the SBC perception, perception of principal leadership, and governance of ICT is able to explain the performance of high school teachers in the district of Cilacap at 77.90 percent, while 22.10 percent is the variation of other variables outside of the studied variables.The conclusions of this study are that: first the perception on the curriculum has a positive influence on the performance of high school teachers. Second perception on school principal leadership has a positive influence on the performance of high school teachers. Third Mastery of ICT has a positive influence on the performance of high school teachers. Fourth perception on SBC, perception on the leadership of principal, and mastery of ICT together have a positive influence on the performance of high school teachers. Fifth mastery of ICT is a factor that has the most dominant influence on the performance of high school teachers in the Cilacap Regency. Keywords: Perception, SBC, School Principal Leadership, mastery of ICT and Teachers performance at school.